Las representaciones de la revolución cubana en la sociedad colombiana: Construcción de imaginarios sociales para la justificación de estados de sitio. 1959-1961 (2016)
This written notice of mental representations of the Cuban revolution between 1959 and1961, created by the mainstream press and that directly impact on Colombian society.The central approach is that the financial aid proposed by the United States for LatinAmerican countries in its strategy called “Alliance for Progress”, demanded that the politicalelite and Colombian society constituted to Cuba and its revolution as the international“political enemy” to which was to attack. Similarly, creating a scene of distress against apossible invasion of Cuba in the internal affairs Colombian served as justification for theimplementation of states of siege in the early years of the National Front. In this regard, thepress played a key role in building-mental instrumental that contributed to such purposes.